Vancomycin AUC(24)/MIC Ratio in Patients with Complicated Bacteremia and Infective Endocarditis Due to Methicillin-Resistant Staphylococcus aureus and Its Association with Attributable Mortality during Hospitalization - Brown, Jack (American Society for Microbiology, 2012)
Methicillin-resistant Staphylococcus aureus (MRSA) is a common cause of complicated bacteremia (CB) and infective endocarditis (IE). The gold standard treatment for these infections is vancomycin. A vancomycin area under the concentration-time curve from 0 to 24 h (AUC(24))/MIC ratio of >400 has been suggested as a target to achieve clinical effectiveness, and yet to date no study has quantitatively investigated the AUC(24)/MIC ratio and its association with attributable mortality (AM). We performed a review of patients treated for MRSA CB and IE from 1 July 2006 to 30 June 2008. AM was defined as deaths where CB or IE was documented as the main cause or was mentioned as the main diagnosis. Classification and regression tree analysis (CART) was used to identify the AUC(24)/MIC ratio associated with AM. Mann-Whitney and Fisher exact tests were used for univariate analysis, and logistic regression was used for multivariate modeling. The MICs were determined by Etest, and the AUC(24) was determined using a maximum a posteriori probability-Bayesian estimator. A total of 32 CB and 18 IE patients were enrolled. The overall crude mortality and AM were 24 and 16%, respectively. The CART-derived partition for the AUC(24)/MIC ratio and AM was <211. Patients with an AUC(24)/MIC ratio of <211 had a >4-fold increase in AM than patients who received vancomycin doses that achieved an AUC(24)/MIC ratio of ≥211 (38 and 8%, respectively; P = 0.02). In bivariate analysis the APACHE-II score and an AUC(24)/MIC ratio of <211 were significantly associated with AM. In the multivariate model, the APACHE-II score (odds ratio, 1.24; P = 0.04) and a vancomycin AUC/MIC ratio of <211 (odds ratio, 10.4; P = 0.01) were independent predictors of AM. In our analysis, independent predictors of AM were the APACHE-II score and an AUC(24)/MIC ratio of <211. We believe further investigations are warranted.